Nutrition: The position in English to-day - M'Gonigle, G. C. M. (George Cuthberth Mura), -1939 (London : Industrial Christian Fellowship)
1936-11 1936 1930s 15 pages CIVILISATION has, throughout its various stages, brought many blessings to mankind. Some of these blessings are material in nature, others are spiritual, and not least among the spiritual manifestations has been the development of a social conscience, which stirs a people to attempt to ameliorate the lot of the oppressed. Twentieth-century England prides itself upon its spirit of humanity, and even boasts that this spirit is a prerogative of our own times, forgetful that other, long-dead, civilisations were similarly moved towards humanitarian policy in national administration. The civilisation of ancient Rome (developed in harshness and ruthlessness) mellowed as the years passed; and the Roman conscience developed a social humanitarianism which, for instance, ameliorated step by step the lot of the slave, till slavery, in its original sense, ceased to exist. It was the public conscience of Rome which forced this change upon the social organisation. Public conscience in England will not knowingly allow malnutrition to persist, once it is convinced that it really does exist and that it is remediable. The social history of the past hundred years in England is a record of a gradual appreciation of preventable ills and of measures designed to ameliorate them. Conditions of life have from time to time been modified by legislation enacted by Parliament as a result of the pressure of public opinion. Hours of labour have been shortened, child labour virtually abolished, 3 15X/2/217/2